A rationally designed bifunctional oxygen electrocatalyst based on Co2P nanoparticles for Zn–air batteries. Issue 15 (14th July 2020) - Shi, Qing; Zheng, Yapeng; Li, Weijun; Tang, Bin; Qin, Lin; Yang, Weiyou; Liu, Qiao
Abstract : A highly-efficient Co2 P-based bifunctional oxygen catalyst has been developed though an enhanced coupling with N, P co-doped carbon nanoparticles and 3D carbon networks, which exhibits better bi-catalytic performance than benchmark noble metal-based counterparts. Abstract : Developing highly cost-effective bifunctional oxygen electrode catalysts for metal–air batteries is urgent but remains challenging. In this paper, we report a highly-efficient Co2 P-based bifunctional oxygen electrocatalyst that comprises Co2 P and N, P co-doped carbon nanoparticles anchored within three-dimensional carbon nanofiber networks (denoted as Co2 P-NPC/CF) through a toxic-free, one-pot synthesis involving in situ growth of Co3 (PO4 )2 –polydopamine/bacterial cellulose (BC) that can be transformed into Co2 P-NPC/CF by a subsequent pyrolysis process. This catalyst exhibits a positive half-wave potential ( E 1/2 ) of 0.85 V for the oxygen reduction reaction, and a low operating potential of 1.60 V at 10 mA cm −2 ( E j10 ) for the oxygen evolution reaction, superior to the benchmark Pt/C (0.82 V) and RuO2 (1.62 V) catalysts, respectively. The reversible oxygen electrode index (Δ E = E j10 − E 1/2 ) is just 0.75 V for Co2 P-NPC/CF, surpassing those for the state-of-the-art noble-metal catalysts (Δ E = 0.80 V for Pt/C–RuO2 ) and most Co-based bifunctional catalysts ever reported. Furthermore, Co2 P-NPC/CF-based primary Zn–air batteries can discharge at 10 mA cm −2 for 110 h with a small voltage loss of 55 mV, and the maximum power density reaches 160 mW cm −2 ; Co2 P-NPC/CF-based rechargeable Zn–air batteries show a negligible voltage gap change after 160 charge–discharge cycles, much better than Pt/C-based batteries. The enhanced bicatalytic performance of this Co2 P-based catalyst can be ascribed to the structural integration of Co2 P NPs with CF networks and N, P co-doped carbon in a synergistic manner, where porous CF networks with a large specific surface area allow for uniform distribution and full exposure of dual active sites, and the simultaneous doping of P and N atoms in carbon could induce an enhanced coupling of Co2 P NPs with N, P-codoped carbon. This work not only provides an easy and safe way to prepare excellent Co2 P-based bifunctional catalysts for Zn–air batteries, but also demonstrates a viable structural integration strategy to offer reference for the design of multifunctional catalysts.